Socialization for Parents to Implement Emotional Strategies in Facing Children's School Admission Selection - Isabella Hasiana; Aisyah Aisyah; Dia Eka Wati; Aprilia Kumalasari (PT. Intelektiva Global Nusantara, 2025)
The purpose of the community service is to provide parents with skills to support their children emotionally and help them manage feelings of anxiety and increase their self-confidence. School entrance exams often create stress that can affect children's emotional well-being and the parent-child relationship. This activity uses a participatory approach and is conducted in three stages: preparation, implementation, and evaluation. Participants were 25 parents in Sidoarjo who have children who will take part in school entrance exams at the junior high and high school levels. The results showed that all participants (29%) experienced an increased understanding of the importance of emotional strategies. Twenty-six percent of participants showed a change in attitude to become calmer and more supportive, and 24% began implementing emotional strategies at home. Furthermore, 21% reported a positive impact on their children's emotional readiness. The findings from this activity indicate that the socialization of emotional strategies effectively increases parents' awareness and skills in supporting their children psychologically, thus helping to create a more stable emotional state and prepare them for school entrance exams.